The Work of Stone Pillars Damaged During Operation - Klymenko, Ievgenii; Grynyova, Iryna; Pents, Volodymyr (International Journal of Engineering and Technology, 2018)
During the experimental and statistical research the experiment was planned for the three most important factors influencing the residual load-bearing capacity of damaged stone columns rectangular cross section, namely, the depth of damage, the angle of the front damage on one of the main sections of soy and eccentricity. Numerical modeling of work of the eccentrically compressed rectangular cross section damaged during the operation of stone pillars was carried out in the LIRA-SAPR software package in a non-linear environment. The results of experimental statistical modeling made it possible to determine the influence on the throughput of each of the selected factors, as well as the mutual influence of the factors. Based on the obtained values of the destructive force for 15 column marks, in accordance with the experimental design, a three-factor experimental-statistical model of the second order was constructed. This model is adequate to the experimental error of 0.45, with 7 statistically significant factors. The analysis of the above method of calculating the damaged stone pillar in PC LIRA allows us to conclude that this method completely takes into account the actual work of the material. The difference between the calculation results and the experimental research of stone structures is within 5%.Â Â